Microstructure and dielectric properties of (Ba,Sr)TiO3 thin film produced by the polymeric precursor method - Pontes, F. M.; Araujo, E. B.; Leite, E. R.; Eiras, J. A.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Pereira-da-Silva, M. A. (Materials Research Society, 2000)
BaxSr1-xTiO3 (x = 0.6) (BST) thin films were successfully prepared on a Pt(111)/TiO2/SiO2/Si(100) substrate by spin coating, using the polymeric precursor method. BST films with a perovskite single phase were obtained after heat treatment at 700 degrees C. The multilayer BST thin films had a granular structure will a grain size of approximately 60 nm. A 480-nm-thick film was obtained by carrying out five cycles of the spin-coating/heating process. Scanning electron microscopy and atomic force microscopy analyses showed that the thin films had a smooth, dense, crack-free surface with low surface roughness (3.6 nm). At room temperature and at a frequency of 100 kHz, the dielectric constant and the dissipation factor were, respectively, 748 and 0.042. The high dielectric constant value was due to the high microstructural quality and chemical homogeneity of the thin films obtained by the polymeric precursor method.